Psychology in Malaysia : looking ahead - Noor, Noraini M. (Pearson Malaysia, 2012)
In the Malaysian context, because of the embeddedness of the individual within groups and a society that is still negotiating itself between the past and present, this final chapter emphasizes three main points; the recognition that many individual-based psychological problems may be reflections of other family and/or group dynamics, and that they may also have structural roots; the dilemma faced by individuals in striking a balance between the traditional and the modern; and in light of these two earlier points, the challenges that psychologists need to confront to make themselves relevant and effective.